ISPC Commentary on the EOIs - Capacity Development - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2015)
ISPC Commentary on the Expressions of Interest (EOIs) for the CGIAR Coordinating Platform on Capacity Development.